Rotating Cantilever Beam Dynamic Strain Measurement and Analysis Based on FBG - Jiang Xi-Xin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The main form of machine’s working principle is rotation. The mechanical properties of rotating component is significant importance to improve the machine’s reliability. In the measurement, the difficult thing is to transmit signals form sensors on a rotor to a stationary part . In this paper, using the FBG’s(Fibre Bragg Gauge)  properties of wireless transmission, author measure the local strains of rotating cantilever beam cantilever by utilizing the strain principle gauge FBG(Fibre Bragg Gauge) and the rotary signal transmit equipment,. The result of analysis showed that rotating cantilever have complicate dynamic phenomenon, dynamic strain not only related to speed but also related to fluid action, the dynamic stiffing phenomenon were observe in the same time. Finally, author offer an improved insight into a strain measurement technique for a rotating mechanical system. The research work could provide an effective way for measuring rotating component’s mechanical properties. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2690